26.1k views
4 votes
5x + 4x - 6x = 24
What’s the answer?

User BenjyTec
by
5.9k points

2 Answers

3 votes

5X + 4X - 6X = 24

9X - 6X = 24

3X = 24

X = 24 : 3

X = 8

User Tom J Nowell
by
6.0k points
7 votes

Answer: 8

Explanation: To solve this equation, we first need to combine like terms on the left side of the equation. Like terms can be added together by simply adding their coefficients.

So in this problem, since 5 + 4 - 6 is 3, this mens that 5x + 4x - 6x = 3x.

Now we have the following equation 3x = 24.

To solve for x in this equation, we want to get x by itself on the left side of the equation. Since x is being multiplied by 3, to get x by itself, we need to divide by 3 on the left side of the equation. Since we divided by 3 on the left side, we must also divide by 3 on the right side.

On the left side, the 3's cancel so we are simply left with x. On the right side, we have 24 divided by 3 which is 8.

Now we have x = 8.

User Jmurzy
by
5.5k points